Circulating endothelial microparticles in children with Henoch-Schonlein purpura - Dursun, I.; Dusunsel, R.; Ulger, H.; Poyrazoglu, M. H.; Gunduz, Z.; Patiroglu, T.; Gurgoze, M. K. (Springer, 2008)
[Abstract Not Available]